Statistical information on Western State of Nigeria controlled produce - Western Nigeria Marketing Board (Ibadan : Statistics Section, Western Nigeria Marketing Board, 1973)
Tables on production of cocoa bean.s, purchases, comparative statistics and quantity produced
.
sju 23/01/2019
Loans
Keywords: Farm produce; Nigeria, Western